The reliability and validity of self-reported reproductive history and obstetric morbidity amongst birth to ten mothers in Soweto - GTH Ellison; T de Wet; KP Matshidze; P Cooper (AOSIS, 2000)
Objective: To assess whether self-reports of reproductive history and obstetric morbidity provide an accurate basis for clinical decision-making. Setting, participants and methods: Self-reports of maternal age and reproductive history, together with clinical measurements of five medical disorders, were abstracted from the obstetric notes of 517 mothers whose children were enrolled in the Birth to Ten study. These data were compared to self-reported information collected by interview during the Birth to Ten study. Findings: The reliability of self-reported age and gravidity was high (R=0.810-0.993), yet self-reports of previous miscarriages, terminations, premature- and stillbirths were only fairly reliable (Kappa=0.48-0.50). Self-reported diabetes and high blood pressure had specificities of more than 95% for glycosuria, hypertension and pre-eclampsia. However, the specificity of self-reported oedema for hypertensive disorders and the specificity of self-reported urinary tract infection for STD seropositivity were only around 65%. Conclusions: The modest reliability and limited validity of self-reported obstetric morbidity undermines the clinical utility of this information. Recommendations: These results strengthen the case for providing mothers with "Home-based Maternal Records" to facilitate access to accurate obstetric information during subsequent clinical consultations.